Proceedings of the Statistical and Social Inquiry Society of Ireland - One Hundred and Seventy-Eighth Session: 2024/2025 - SSISI (Statistical and Social Inquiry Society of Ireland, 2025)
Proceedings of the Statistical and Social Inquiry Society of Ireland - One Hundred and Seventy-Eighth Session: 2024/2025
Proceedings of the Statistical and Social Inquiry Society of Ireland - One Hundred and Seventy-Eighth Session: 2024/2025
Keywords: proceedings; 314.15